Variação gênica e estrutura populacional de Euglossa cordata (Linnaeus, 1758) acessadas por meio de marcador mitocondrial e locos microssatélites - Gória, Paula Salles (2018)
Orchid bees (Apidae, Euglossini) are important Neotropical pollinators. Two main features characterize these species: the tongue, which reaches at least half the body length, enabling the search for food resources in general, and the habit on the part of males of collecting aromatic compounds from various plant sources, which is a behavior that is unclearly associated with reproduction. Euglossa cordata is commonly found in cities and has primitive social behavior. Its nests are generally small and often reactivated in relationships between mothers and daughters, sisters or even unrelated females. Although Eg. cordata has been widely studied with regard to ecological and sociogenetic aspects, few studies have investigated how its occupation of the different environments occurs or its patterns of distribution over larger areas, especially with the use of more than one type of molecular marker. The 229 specimens analyzed were from 13 different Brazilian states distributed among the five major geographical regions (central, northeastern, northern, southeastern and southern Brazil). Genetic analysis were performed to verify the suggested sex-biased dispersal pattern, as well as determine population structuring and genetic diversity through the analysis of the mitochondrial 16S gene fragment and 15 microsatellite loci. The 20 characterized haplotypes showed considerable haplotype diversity and low nucleotide diversity. The results of the mitochondrial marker analysis also indicate certain genetic heterogeneity among populations, whereas the microsatellite loci indicate greater homogeneity among populations, which is explained by the relationship between dispersal and occupation of the environments by each of the sexes. The occurrence of gene flow, the presumed high number of individuals, the absence of diploid males and the great allelic diversity found suggest a health population. In addition, this work recovered a discussion about the difficulty of amplification of the mitochondrial genes COI and CytB for this species. The data also point to the existence of distinct population groups associated with the coastal and inland regions of the country, suggesting two dispersal routes, which underscores the need for further studies on the species, involving, for example, phylogeographic analysis.